Improved hydroxypropyl methylcellulose (HPMC) films through incorporation of amylose-sodium palmitate inclusion complexes. (15th May 2018) - Hay, William T.; Fanta, George F.; Peterson, Steven C.; Thomas, A.J.; Utt, Kelly D.; Walsh, Kathleen A.; Boddu, Veera M.; Selling, Gordon W.
Highlights: Novel method for incorporating lipid into HPMC. Films of HPMC and amylose complexes have improved physical properties. HPMC polymer blended films produced having increased thermal resilience. HPMC polymer blended films produced having reduced oxygen permeability. HPMC polymer blended films produced having reduced water permeability. Abstract: Polymer film blends of hydroxypropyl methylcellulose (HPMC) and amylose-sodium palmitate inclusion complexes (Na-Palm) were produced with no plasticizer, and were observed to have improved physical and gas barrier properties as compared with pure HPMC. The crystalline amylose helices incorporating the hydrophobic sodium palmitate ligand decreased the water vapor permeability of a 50/50% blended film of HPMC/Na-Palm by 40% and decreased oxygen permeability by 96%. The incorporation of 25% Na-Palm into HPMC films resulted in improved elongation, Young's modulus and toughness. Addition of the amylose-complexes produced relatively smooth, high clarity films which had reduced solubility in neutral and acidic solutions. Increasing concentrations of Na-Palm increased film thermal resilience and increased storage modulus at high temperatures. The heat deflection temperature of the films also increased with increasing concentrations of amylose-complex; HPMC/Na-Palm film blends with >50% Na-Palm displayed almost no material deformation up to 250 °C.